Contributions of Hedgerows to People: A Global Meta-Analysis - García de León, David; Rey Benayas, José M.; Andivia, Enrique (Frontiers in Conservation Science, 2021)
Hedgerows are linear landscape features of woody vegetation usually located around agricultural fields. An increasing number of studies have addressed the effects of hedgerows on biodiversity and ecosystem services. This study aims to synthetize these effects and compare levels of biodiversity and ecosystem services in farmland with hedgerows and (1) farmland without hedgerows and (2) nearby natural habitat at the global scale. We hypothesized that farmland with hedgerows (1) enhance biodiversity and ecosystem services as compared to farmland without hedgerows but (2) support lower levels of biodiversity and ecosystem services than natural habitat. Our systematic literature review retained 835 observations from 170 primary studies, which were analysed following standard methodology in meta-analyses. Our results partially support both hypotheses. Farmland with hedgerows exhibited higher levels of biodiversity and provisioning services than farmland without hedgerows (H1). Farmland with hedgerows provided similar levels of biodiversity (edge effects) but lower levels of ecosystem services than natural habitat (H2). The effects of hedgerows on biodiversity and ecosystem services depended on control ecosystem type (grassland/meadow or forest/woodland) but were largely independent of climate type (temperate or tropical) and the focus of spatial scale (field or landscape). In conclusion, conservation and restoration of hedgerows contribute to people in several ways by enhancing biodiversity and multi-functionality in agricultural landscapes.